Nutrient concentration during June to July 2018 in the South China Sea - Jin, Xiaobo; Liu, Chuanlian (PANGAEA, 2021)
Approximate 0.5 L water samples at full depth for macronutrient (nitrate+nitrite, phosphate, silicate) analysis were collected with a CTD sampler in the South China Sea, boarding scientific research vessel “Tan Kah Kee” during NSFC cruise NORC2018-5 (KK1804-2) on June to July 2018. The nutrient concentrations were determined on board, with a classical colorimetric method using a BRAN-LUEBBE AA3 Auto-Analyzer. The detection limit is 0.1 μmol/L for nitrate+nitrite, 0.08 μmol/L for phosphate, and 0.16 μmol/L for silicate, respectively.
Keywords: June-July; macronutrient concentration; nitrate; nitrite; Phosphate; silicate; South China Sea